Position-specific longitudinal assessment of total and regional body composition in NCAA Division I football players - Brooks, S. G.; Dengel, D. R. (The Journal of Strength and Conditioning Research, 2026)
Position-specific differences in body composition in American football players have been established. How the total and regional composition changes from preseason to postseason by position is unknown. Thus, this study examined longitudinal changes in total and regional body composition in NCAA Division I collegiate football players (CFPs) over a competitive season. A total of 188 male CFPs aged 18-23 (20.7 ± 1.6 years) were included. Body composition was measured using dual X-ray absorptiometry at preseason and postseason. Subjects were grouped into defensive backs, defensive linemen, linebackers, offensive linemen, punters/kickers, quarterbacks, running backs, tight ends, and wide receivers. Repeated-measures ANOVA assessed effects of season and position on total and regional body composition, controlling for player participation status. Post hoc pairwise comparisons determined the magnitude, direction, and significance of changes for each position. There were no changes in total or regional measures of body mass, fat mass, or bone mass across the season, except for arm mass. Significant (p < 0.05) decreases in total lean mass (LM), arm LM, leg LM, and gynoid LM were observed in certain position groups. The results of this study confirm that there is a decrease in total LM during a competitive season in CFPs. This study demonstrates that this loss in LM mainly comes from the leg and gynoid regions of the body and occurs across all positions. This information can be used by strength and nutrition staff to develop new strategies to prevent this LM loss during the season.